2019
DOI: 10.1074/mcp.ra118.001102
|View full text |Cite
|
Sign up to set email alerts
|

Common Metabolic Pathways Implicated in Resistance to Chemotherapy Point to a Key Mitochondrial Role in Breast Cancer*

Abstract: Quantitative MS-based proteomics enabled to distinguish metabolic differences of triple negative breast cancer cells and corresponding chemoresistant and cancer stem cells (CSC). This puts mitochondria in a spotlight for cancer therapy and places bactericidal antibiotics;particularly linezolid-as effective agents for eliminating CSC and resistant cells. Graphical Abstract Highlights• OMICS distinguish cancer cells from resistant or cancer stem cells.• Bactericidal antibiotics and mitochondria.• Linezolid and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Furthermore, the use of antidiabetic drugs including metformin and GLP1 mimetics showed promising results in animal models of AD (Jha et al, 2017;Holscher, 2018). Moreover, considering that insulin signaling activation regulates mitochondrial functions (Butterfield et al, 2014a;Abad et al, 2019;Wardelmann et al, 2019) and that mitochondria are dysfunctional in DS (Mollo et al, 2020), it is conceivable to think rescuing insulin signaling activation in DS would be beneficial also with respect to mitochondrial performances. Metformin, a well-known drugs used to treat insulin resistance, was effective in recovering mitochondrial structure and functions in trisomic cells (Izzo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the use of antidiabetic drugs including metformin and GLP1 mimetics showed promising results in animal models of AD (Jha et al, 2017;Holscher, 2018). Moreover, considering that insulin signaling activation regulates mitochondrial functions (Butterfield et al, 2014a;Abad et al, 2019;Wardelmann et al, 2019) and that mitochondria are dysfunctional in DS (Mollo et al, 2020), it is conceivable to think rescuing insulin signaling activation in DS would be beneficial also with respect to mitochondrial performances. Metformin, a well-known drugs used to treat insulin resistance, was effective in recovering mitochondrial structure and functions in trisomic cells (Izzo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In metabolomic and proteomic studies, our group has recently demonstrated common regulatory pathways to distinguish resistant cancer cells (non-CSCs) and CSCs from parental cells using a breast cancer model [13]. Hence, it is of major relevance to focus on those proteins present in resistant cancer cells and CSCs in order to design more effective treatment strategies that might synergistically act with standard chemotherapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning breast cancer, it is one of the most commonly diagnosed cancers worldwide, generally known as metastatic cancer resistant to chemotherapy (19,20). Therefore, many investigations are focused on finding new drugs and drug delivery systems to fight it.…”
Section: Introductionmentioning
confidence: 99%